ANALISIS PENGARUH LIKUIDITAS SAHAM, EARNING PER SHARE, RETURN SAHAM, HARGA SAHAM, DAN VOLUME PERDAGANGAN SAHAM TERHADAP KEPUTUSAN STOCK SPLIT - Nofita Sari; Zaenal Afifi; Diah Ayu Susanti (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2024)
Stock split is an action carried out by a company by dividing the nominal value of shares into smaller so that the number of outstanding shares becomes more. This study aims to test and analyze the effect of stock liquidity, earnings per share, stock return, stock price, and stock trading volume on stock split decisions in companies listed on the Indonesia Stock Exchange in 2018-2022. The population used in this study is all companies listed on the Indonesia Stock Exchange during 2018-2022. The technique used for sampling in this study is purposive sampling technique, with a total of 85 company samples produced. The research method uses the logistic linear regression analysis method with SPSS software tool version 25. The results of this study show that stock liquidity, earnings per share, stock price, and stock trading volume have no influence on stock split decisions. Meanwhile, stock returns have a positive influence on stock split decisions.